Zen & philosophy : an intellectual biography of Nishida Kitarō - Yusa, Michiko (University of Hawai'i Press, 2002)
This is the definitive work on the first and greatest of Japan's twentieth-century philosophers, Nishida Kitaro (1870-1945). Interspersed throughout the narrative of Nishida's life and thought is a generous selection of the philosopher's own essays, letters, and short presentations, newly translated into English.